Quantifying vegetation health exposure risk and spatial inequality along with their impact on vegetation - Peng Zhou; Jieming Chou; Mengting Sun; Weixing Zhao; Yuanmeng Li; Hongze Pei; Haofeng Jin; Muhammad Bilal (International Journal of Digital Earth)
Air pollution poses significant threats to vegetation health due to climate change and human activities. This study introduces a new remote sensing method to assess the impact of air pollution on vegetation health across China, introducing a Vegetation Exposure Intensity (VEI) index based on a weighted calculation that combines the Normalized Difference Vegetation Index (NDVI) with six air pollutants. Using Partial Least Squares Structural Equation Modeling (PLS-SEM) and the Gini index, the study reveals that from 2013 to 2022, air pollution exposure is more unequal in western regions compared to the east, with notable spatiotemporal variations in Beijing-Tianjin-Hebei and the Yangtze River Delta. High pollution exposure correlates with vegetation degradation, particularly in ecologically vulnerable areas in central and southern China. Climate factors, especially rising temperatures and vapor pressure, increase VEI, while wind speed helps reduce it. This research provides insights into the ecological impacts of air pollution exposure and informs regional ecological protection policies.